Heating in ultraintense laser-induced shock waves. (3rd April 2017) - Eliezer, Shalom; Pinhasi, Shirly Vinikman; Martinez Val, José Maria; Raicher, Erez; Henis, Zohar
Abstract: This paper considers the heating of a target in a shock wave created in a planar geometry by the ponderomotive force induced by a short laser pulse with intensity higher than 10 18 W/cm 2 . The shock parameters were calculated using the relativistic Rankine–Hugoniot equations coupled to a laser piston model. The temperatures of the electrons and the ions were calculated as a function of time by using the energy conservation separately for ions and electrons. These equations are supplemented by the ideal gas equations of state (with one or three degrees of freedom) separately for ions and electrons. The efficiency of the transition of the work done by the laser piston into internal thermal energy is calculated in the context of the Hugoniot equations by taking into account the binary collisions during the shock wave formation from the target initial condition to the compressed domain. It is shown that for each laser intensity there is threshold pulse duration for the formation of a shock wave. The explicit calculations are done for an aluminum target.